Complete genome sequence of the halophilic and highly halotolerant Chromohalobacter salexigens type strain (1H11(T)) - Copeland, Alex (Michigan State University, 2011)
Chromohalobacter salexigens is one of nine currently known species of the genus Chromohalobacter in the family Halomonadaceae. It is the most halotolerant of the so-called ‘moderately halophilic bacteria’ currently known and, due to its strong euryhaline phenotype, it is an established model organism for prokaryotic osmoadaptation. C. salexigens strain 1H11(T) and Halomonas elongata are the first and the second members of the family Halomonadaceae with a completely sequenced genome. The 3,696,649 bp long chromosome with a total of 3,319 protein-coding and 93 RNA genes was sequenced as part of the DOE Joint Genome Institute Program DOEM 2004.